Gambaran Perilaku Caring Petugas Lembaga Pembinaan Khusus Anak - Sri Maslihah; Muhammad Ariez Musthofa; Gemala Nurendah (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aims to obtain empirical data about caring behavior of warden in child prison (LPKA) perceived by child inmates called LPKA students. This study used mixed-method design combining quantitative and qualitative approaches. The first phase of research conducted by quantitative methods of data collection involving 67 samples consisted of 44 students of LPKA Bandung and 23 students of LPKA Tangerang. The measuring instrument used was caring behavior questionnaire adapted from Freese's caring instrument (1999). The second phase was conducted through interviews with four students of LPKA. The results showed that the caring behaviors of LPKA officers were mainly shown in the dimensions of understanding LPKA students. The caring behavior of these officers is demonstrated by their concern for physical conditions, food needs and emotional assistance, especially when LPKA students face problems. The presence of officers who care for LPKA students might be able to substitute the parents figures for LPKA students.